Nanofibrous membranes reveal better properties for culturing of RPE cells in comparison with commercial scaffolds - Ardan, Taras; Zemanova, Lucie; Ellederova, Zdenka; Drutovič, Saskia; Studenovská, Hana; Popelka, Stepan; Kepkova‐Vodickova, Katerina; Rohiwal, Sonali; Sedlackova, Miroslava; Motlik, Jan (Acta ophthalmologica (Oxford, England), 2019)
Purpose Malfunction of the retinal pigment epithelium (RPE) is a cause of the whole row of retinal degenerative diseases such as age related macular degeneration (AMD). RPE replacement based on transplantation of cultured RPE cells on artificial membranes into the retina can be a perspective way for the therapy of these incurable diseases. Methods Porcine primary RPE cells were isolated from cadaverous porcine eyes on two types of artificial membranes: commercial polyester scaffolds Transwell and polylactate nanofibrous membrane manufactured by us. Both membranes have the same pore sizes. For the detection of important functional and morphological markers of RPE cells, we used three types of assays ‐ immunocytochemistry, real‐time qPCR and electron microscopy. The ultrastructure of cultured RPE cells was examined by scanning and transmission electron microscopy (EM). Results Using real‐time qPCR assay, we found that cultured cells on nanofibrous membranes demonstrated higher expressions of mRNAs typical for RPE cells. Moreover, immunocytochemical detection of cultured cells on nanomembranes revealed more intensive staining of all important markers in comparison with commercial ones. Electron microscopy of both membranes confirmed a confluent layer of RPE cells and their correct morphological structure, which was comparable with the cells of native RPE. Only on nanofibrous scaffolds and using scanning EM we found the better development of RPE cilia. Conclusion Our results enable us to conclude that RPE culturing on nanomembranes improved the final quality of RPE cells by better maturation and long‐term survival of RPE monolayer in contrary with culturing on commercial scaffolds. Such cultured RPE cells are fully able to replace non‐functioning native RPE cells during cell therapy.